2009
DOI: 10.1590/s1678-58782009000300012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-singular BEM algorithms for potential problems

Abstract: Two non-singular boundary element method (BEM) algorithms for two-dimensional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The acoustic sources are extracted from the transient flow field data and then a wave equation, derived from Lighthill's acoustic analogy, is solved to predict the propagation of these acoustic sources. Gloerfelt et al [5] demonstrated that the surface distribution of for hypersingular integrals often results in oscillatory solutions with high errors [25]. He showed that the contribution of a stationary rigid body on the sound generated by unsteady flow is equivalent to a surface distribution of acoustic dipoles computed from the instantaneous pressure fluctuations on the body.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The acoustic sources are extracted from the transient flow field data and then a wave equation, derived from Lighthill's acoustic analogy, is solved to predict the propagation of these acoustic sources. Gloerfelt et al [5] demonstrated that the surface distribution of for hypersingular integrals often results in oscillatory solutions with high errors [25]. He showed that the contribution of a stationary rigid body on the sound generated by unsteady flow is equivalent to a surface distribution of acoustic dipoles computed from the instantaneous pressure fluctuations on the body.…”
Section: Introductionmentioning
confidence: 99%
“…Curle [3] extended Lighthill's analogy to consider the effect of stationary boundaries present in the turbulent flow on the sound generation. For hypersingular BEM, discontinuous elements that satisfy the continuity requirement in the element interior, but are discontinuous across element boundaries, have been developed [25]. Powell [4] argued that forces acting on a rigid body due to the fluctuating hydrodynamic pressure cannot produce acoustic fluctuations as the boundary is fixed and cannot vibrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strategy similar to the use of non-conforming element but with the same size of system matrix as in displacement-BIE, was used in two-dimensional elastodynamics by Gallego and Dominguez (1996). Ribeiro et al (2009) implemented this scheme for two-dimensional potential problems, and 3-D acoustic problems were treated in Liu and Chen (1999) using the scheme. and Dominguez et al (2 0 0 0 ) adopted this strategy for three-dimensional fracture problem where traction-BIE is only applied to elements on the crack surface while for the other elements in the problem, the displacement-BIE is applied.…”
Section: T Raction-bie and H Yp Ersin Gu Lar-b Iementioning
confidence: 99%